2009
DOI: 10.1016/j.rbmo.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Chromomycin A3 staining, sperm chromatin structure assay and hyaluronic acid binding assay as predictors for assisted reproductive outcome

Abstract: Functional sperm tests such as the sperm chromatin structure assay (SCSA), chromomycin A3 staining (CMA(3)) and hyaluronic acid binding assay (HBA) have been suggested as predictive tests of fertility in vitro. This study aimed to define the clinical role of these functional parameters in assisted reproduction in a prospective cohort study. Conventional sperm diagnosis (motility, morphology and concentration) as well as SCSA, CMA(3) and HBA tests were performed on 205 semen samples [74 IVF, 94 ICSI and 37 comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 100 publications
2
32
0
3
Order By: Relevance
“…Similarly to us, in a recent report Tarozzi et al, found no association between HA binding and fertilization rate, cleavage rate and embryo quality [26]. Nijs et al, studied Values are expressed as mean±standard deviation [27]. In our study morphology was not assessed on the day of fertilization.…”
Section: Discussionsupporting
confidence: 68%
“…Similarly to us, in a recent report Tarozzi et al, found no association between HA binding and fertilization rate, cleavage rate and embryo quality [26]. Nijs et al, studied Values are expressed as mean±standard deviation [27]. In our study morphology was not assessed on the day of fertilization.…”
Section: Discussionsupporting
confidence: 68%
“…According to SCSA studies, the percentage of red sperm in this method represents the DF in sperm population, which is related to DNA break or protamination defects, while sperms with green color indicate immature spermatozoa [36]. This finding confirms the Nijs et al [37] study that showed that the percent of HBA correlated inversely with evaluated HDS and did not find any important association between HBA and DF. In addition, Nasr-Esfahani et al [38] did not observe any relationship between studied DF through sperm chromatin dispersion test and HBA.…”
Section: Discussionsupporting
confidence: 62%
“…In another report the clinical outcome of sperm functional assays including HBA was studied [Nijs et al 2009]. A correlation of HA-binding was found with morphology, but it did not predict FR and CPR.…”
Section: Discussionmentioning
confidence: 99%